A simple and efficient method to extract polar metabolites from guar leaves (Cyamopsis tetragonoloba (L.) Taub.) for GC-MS metabolome analysis - S. B. Teplyakova; A. L. Shavarda; T. V. Shelenga; E. A. Dzyubenko; E. K. Potokina (Вавиловский журнал генетики и селекции)
Guar (Cyamopsis tetragonoloba (L.) Taub.) is an agricultural crop species new to Russia and is in demand by the gas, oil and food industries. Due to the progress of “omics” technologies and the marker-assisted selection, there is a huge interest in the studies that compare the metabolites of various guar varieties, employing metabolomics as a method of functional genomics. For a large-scale screening of guar germplasm from the VIR collection, it is important to choose an efficient method to extract metabolites from samples. The accuracy of the assessment of the content of metabolites in samples is crucial for distinguishing varieties within the crop, since the metabolome profiles of plants within the same species differ mainly in the quantitative ratio of metabolites, and not in their qualitative composition. In metabolome practice, two methods of extracting polar compounds are usually employed in the preparation of samples for GC-MS analysis. One of the widely used methods of sample preparation is the long-term extraction of metabolites from whole tissues with the aid of a methanol solvent. Another method of sample preparation is based on the short-term methanol extraction of metabolites from frozen and homogenized material. The advantages and disadvantages of these two methods revealed in the course of our work have prompted us to develop a new approach that avoids some difficulties in analyzing the metabolic profiles of leaves of various guar varieties. The method we suggested combines the advantages of the two above-mentioned approaches of sample preparation, namely eliminates the loss of metabolites due to centrifugation and ensures the complete destruction of all cell walls, ensuring the maximum extraction level of polar metabolites. The essence of the new method is that the leaf is rapidly frozen in liquid nitrogen with subsequent thawing in cold methanol. Thus, leaf tissues retain morphological integrity, and subsequent centrifugation, necessary for homogenization, is skipped. We have checked the effectiveness of this improved method by experiments with leaf samples of three guar genotypes. It has been shown that the amount of extracted metabolites increases more than 5-fold compared to extraction with methanol from fresh unfrozen leaf tissues and more than 2-fold compared to extraction with methanol after freezing and homogenization. Extraction of metabolites using the new method allows the GC-MS analysis of guar samples to be conducted with the least loss and high accuracy required to distinguish varieties.